Optimization of sound absorption of recycled Nylon fibrous materials - Biboud, Julien; Elkoun, Saïd; Panneton, Raymond (Frontiers in Acoustics, 2024)
A semi-empirical model for the assessment and an optimization procedure of the sound absorption coefficient of compressed nonwoven fibrous materials made from recycled Nylon fibers (RNF) is developed. In general, the prediction of the sound absorption properties of materials requires the measurement of non-acoustic parameters by specialized characterization tools that are not always within reach of most laboratories. The objective of the proposed model is to establish empirical relationships between these non-acoustic parameters and the bulk density of RNF materials. These empirical relationships are then substituted into a conventional acoustic model for porous materials, namely the model of Johnson-Champoux-Allard. The proposed model accurately predicts the sound absorption coefficients of compressed RNF materials based solely on bulk density, thickness, and frequency. This prediction is validated through impedance tube measurements. Moreover, the model is used with a proposed optimization producedure to identify the ideal density and thickness for maximum sound absorption at a specific frequency.Impedance tube measurements on optimized configurations confirm the effectiveness of this optimization process.